Characterizing Early T Cell Responses in Nonhuman Primate Model of Tuberculosis - Sharan, Riti; Singh, Dhiraj Kumar; Rengarajan, Jyothi; Kaushal, Deepak (Frontiers in Immunology, 2021)
Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb), remains a leading infectious disease killer worldwide with 1.4 million TB deaths in 2019. While the majority of infected population maintain an active control of the bacteria, a subset develops active disease leading to mortality. Effective T cell responses are critical to TB immunity with CD4+ and CD8+ T cells being key players of defense. These early cellular responses to TB infection have not yet been studied in-depth in either humans or preclinical animal models. Characterizing early T cell responses in a physiologically relevant preclinical model can provide valuable understanding of the factors that control disease development. We studied Mtb-specific T cell responses in the lung compartment of rhesus macaques infected with either a low- or a high-dose of Mtb CDC1551 via aerosol. Relative to baseline, significantly higher Mtb-specific CD4+IFN-+ and TNF-+ T cell responses were observed in the BAL of low dose infected macaques as early as week 1 post TB infection. The IFN- and TNF-a response was delayed to week 3 post infection in Mtb-specific CD4+ and CD8+T cells in the high dose group. The manifestation of earlier T cell responses in the group exposed to the lower Mtb dose suggested a critical role of these cytokines in the antimycobacterial immune cascade, and specifically in the granuloma formation to contain the bacteria. However, a similar increase was not reflected in the CD4+ and CD8+IL-17+ T cells at week 1 post infection in the low dose group. This could be attributed to either a suppression of the IL-17 response or a lack of induction at this early stage of infection. On the contrary, there was a significantly higher IL-17+ response in Mtb-specific CD4+ and CD8+T cells at week 3 in the high dose group. The results clearly demonstrate an early differentiation in the immunity following low dose and high dose infection, largely represented by differences in the IFN- and TNF- response by Mtb-specific T cells in the BAL. This early response to antigen expression by the bacteria could be critical for both bacterial growth control and bacterial containment.